2022
DOI: 10.48550/arxiv.2204.11868
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Model-agnostic interpretation of 10 billion years of cosmic evolution traced by BOSS and eBOSS data

Samuel Brieden,
Héctor Gil-Marín,
Licia Verde

Abstract: We present the first model-agnostic analysis of the complete set of Sloan Digital Sky Survey III (BOSS) and -IV (eBOSS) catalogues of luminous red galaxy and quasar clustering in the redshift range 0.2 ≤ z ≤ 2.2 (10 billion years of cosmic evolution), which consistently includes the baryon acoustic oscillations (BAO), redshift space distortions (RSD) and the shape of the transfer function signatures, from pre-and post-reconstructed catalogues in Fourier space. This approach complements the standard analyses te… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 105 publications
(188 reference statements)
0
7
0
Order By: Relevance
“…The measurement at z = 0.15 is for the SDSS Main Galaxy Sample (Howlett et al 2015). The open circles show a reanalysis of the BOSS, eBOSS/LRG and eBOSS/QSO samples by Brieden et al (2022) using their ShapeFit methodology. The open diamond shows results from an effective field theory analysis of the eBOSS Emission Line Galaxy sample by Ivanov (2021).…”
Section: Constraints From Redshift Space Distortionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement at z = 0.15 is for the SDSS Main Galaxy Sample (Howlett et al 2015). The open circles show a reanalysis of the BOSS, eBOSS/LRG and eBOSS/QSO samples by Brieden et al (2022) using their ShapeFit methodology. The open diamond shows results from an effective field theory analysis of the eBOSS Emission Line Galaxy sample by Ivanov (2021).…”
Section: Constraints From Redshift Space Distortionsmentioning
confidence: 99%
“…Recently, Brieden et al (2021b,a) have developed an extension of the 'classical' BOSS/eBOSS analyses, by including an additional parameter that is sensitive to the parameter combination Ωmh. The constraints on f σ8 derived by applying their ShapeFit technique to the BOSS, eBOSS/LRG and eBOSS/QSO samples (Brieden et al 2022) are shown by the open symbols in Fig. 2.…”
Section: Constraints From Redshift Space Distortionsmentioning
confidence: 99%
“…While detecting these gravitons is an experimental challenge for the future, the above estimates provide an avenue to test our scenario rather soon. Improvements in theoretical reactions rates relevant to BBN calculations by the LUNA 8 project, as well as further analysis from a large-scale structure by the ShapeFit team Brieden et al (2022), will provide much tighter constrain on the allowed value of ΔN eff during BBN. This can either refute our scenario or support it.…”
Section: Conclusion and Observational Signaturesmentioning
confidence: 99%
“…The most natural path to discover this is via the presence of neutrinoless double beta decay (which is only possible if the neutrinos are Majorana) [2,3]; several experimental efforts around the world, placed in underground laboratories, are trying to detect this signal [4]. However, if the total mass of neutrinos is as small as cosmology suggests (< 0.1 eV [5,6]), then the required size of the detector will be ∼1-10 tons of the double beta decay isotope, which will be challenging. It is therefore interesting to explore other experimental signatures to detect the physical nature of neutrinos.…”
Section: Introductionmentioning
confidence: 99%